Association between media exposure and behavioral problems among preschool children - Mohamed A. Zoromba; Mohamed A. Zoromba; Doaa Abdelgawad; Sahar Hashem; Heba El-Gazar; Magda Ahmed Abd El Aziz (Frontiers in Psychology, 2023)
BackgroundThe prevalence of behavioral problems among preschool children is remarkably increasing in the clinical setting.AimThe current study aimed to investigate the association between media exposure and behavioral problems among preschool children.MethodsThis survey study recruited 560 children from 10 nurseries selected randomly, located in El-Mansoura, Egypt. Tools included socio-demographic characteristics the Media Exposure Questionnaire and the Conners Comprehensive Behavior Rating Scales (CBRS-48).ResultsThe participants were exposed to media for an average of 105.84 min per day and displayed moderate levels in all subscales of CBRS-48. The duration of media exposure was significantly correlated to the hyperactivity index, learning problems, hyperactivity/impulsivity, conduct problem, anxiety, and psychosomatic problems (r = 0.372, 0.356, 0.323, 0.306, 0.298, 0.291, and 0.255, respectively).ConclusionThe duration of media exposure was significantly correlated to the subscales of CBRS-48.Implication for nursing practicePreschool children should be engaged in concrete activities and social interactions that may lessen negative media effects such as hyperactivity, learning problems, hyperactivity/impulsivity, conduct problem, anxiety, and psychosomatic problems.